The effect of nutritional supplements accompanying a training program on some of the physical abilities of soccer referees (Journal of the College of Basic Education, 2022)
Research SummaryThe research aims to:1- Preparing a training program for football referees.2- Putting doses of some necessary nutritional supplements in line with the capabilities of the rulers.3- To identify the effect of the training program on some of the physical abilities of football referees.4- To identify the effect of nutritional supplements accompanying a training program on some of the physical abilities of football referees.The experimental approach was used, and the research sample was selected from first-class football referees accredited by the Iraqi Central Football Association in Baghdad for the 2011-2012 football season, whose number is 30 referees.